Drgania Parametryczne Jednostopniowej Przekładni Zębatej - Gryboś, R. (Engineering Transactions, 1972)
The subject of the investigations is the theoretical analysis of parametric vibrations of a simple gear transmission produced by periodic variations of the toothing rigidity. The equations of motion are written for the transmission gear treated as a model with four degrees of freedom. A simplified model with two degrees of freedom is also proposed taking into account both the torsional rigidity of the shaft and bending rigidity of the tooth. The corresponding equations of motion are also written. The formula for the dynamical coefficient of the tooth loading is derived.